2014
DOI: 10.1111/jth.12644
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen activator‐1 overexpression decreases experimental postthrombotic vein wall fibrosis by a non‐vitronectin‐dependent mechanism

Abstract: SUMMARY Background Factors associated with post-thrombotic syndrome are known clinically, but the underlying cellular processes at the vein wall are not well-delineated. Prior work suggests that vein wall damage does not correlate with thrombus resolution, but rather with plasminogen activator-1 (PAI-1) and matrix metalloproteinase (MMP) activity. Objective We hypothesized that PAI-1 would confer post venous thrombosis (VT) vein wall protection via a Vitronectin (Vn) dependent mechanism. Methods A stasis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 60 publications
0
21
0
Order By: Relevance
“…The reduction of type I and III collagen secretion by VSMC is induced through TGF-β1/Smad3 signaling pathway inhibition [ 93 ]. Expression levels of PAI-1, the major physiological regulator of the plasmin-based pericellular proteolytic cascade, are also linked to TGFβ1-induced neointimal expansion [ 89 ], although the actual role of PAI-1 in the development of a VSMC-rich neointima is likely to be complex [ 94 , 95 ].…”
Section: The Role Of Tgf-β1 Signaling Pathways In Vessel Wall Pathmentioning
confidence: 99%
“…The reduction of type I and III collagen secretion by VSMC is induced through TGF-β1/Smad3 signaling pathway inhibition [ 93 ]. Expression levels of PAI-1, the major physiological regulator of the plasmin-based pericellular proteolytic cascade, are also linked to TGFβ1-induced neointimal expansion [ 89 ], although the actual role of PAI-1 in the development of a VSMC-rich neointima is likely to be complex [ 94 , 95 ].…”
Section: The Role Of Tgf-β1 Signaling Pathways In Vessel Wall Pathmentioning
confidence: 99%
“…Additionally the endothelial cell marker, CD31 and vein wall smooth muscle cell (VSMC) gene expression were enhanced in PAI-1 deficient models, suggesting a role for PAI-1 in endothelial integrity and vein wall remodeling (24). Consistent with this, transgenic mice overexpressing PAI-1 showed impaired thrombus resolution, although paradoxically, had significantly less collagen deposition in the vein wall, resulting in decreased vein wall fibrosis (25). …”
Section: Introductionmentioning
confidence: 68%
“…; Obi et al. ). Deficiencies in plasmin or plasminogen activator have led to increased fibrosis (de Giorgio‐Miller et al.…”
Section: Discussionmentioning
confidence: 96%
“…A review of the literature revealed a precedent with regard to the role of plasminogen in fibrosis. Activation of the plasminogen/plasmin system has been shown to slow progression of fibrosis in experimentally induced asbestos disease for murine models (Hattori et al 2004;Obi et al 2014). Deficiencies in plasmin or plasminogen activator have led to increased fibrosis (de Giorgio-Miller et al 2005).…”
Section: Discussionmentioning
confidence: 99%